Keselarasan antara syariat dan theosofi dalam pembinaan akhlak mahasiswa: Pendekatan akhlak di Ma’had Sunan Ampel Al-Aly UIN Malang - Melodiva, Syafila (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the harmony between the principles of Islamic Sharia and theosophy in the moral development of students at Ma’had Sunan Ampel Al-Aly, UIN Malang. Within the context of Islamic character education, an integrative approach that combines Sharia (formal religious aspects) with theosophy (universal and esoteric divine wisdom) serves as an essential foundation for shaping morally upright, moderate, and spiritually grounded individuals. This research employs a qualitative approach using a case study method. Data were collected through observations, in-depth interviews with Ma’had instructors and students, and document analysis. The findings reveal that moral development at Ma’had is not only based on the formal application of Islamic laws but also instills universal spiritual values such as divine awareness, tolerance, sincerity, and moral responsibility. Theosophy acts as a bridge to deepen the inner meaning of Sharia teachings, creating a balance between the external and internal dimensions of moral formation. This harmony proves effective in shaping students with religious, inclusive, and self-transformative character. The study recommends strengthening this integrative approach within the moral education curriculum in Islamic educational institutions.